Z mikroekonometrii Jana Falewicza - Bartosiewicz, Stanisława; Cieślak, Maria; Rusinek, Kazimierz (Wydział Prawa i Administracji UAM, 1966)
The authors of the paper undertake an attempt to present the main ideas of Jan Falewicz related to the economic problems of enterprises. J. Falewicz used to employ the notion of enterprise for denoting any, at random detached from the whole economic body, clearly defined partial organism. The purpose of setting up and functioning of such an enterprise is to deliver to the exterior "things" socially more useful from "things" which are flowing to it from the exterior. Basing on original definitions of: rentability, economic management and costs, J. Falewicz construes a model of economic activity for enterprises, which on the foundations of established relations between the economic and technical-economic categories constitutes a basis for undertaking proper economic decisions. J. Falewicz represents the view, that a rational way of assessing and settling the costs requires such a dismemberment of enterprise on smaller cells, that from each of them would flow only one kind of produce, irrespectively of the fact whether that produce leaves the enterprise altogether or is transferred to other cells of that particular enterprise as a service rendered to them. The analysis of dismembered and individualized costs is undertaken by J. Falewicz by means of a straightlined regression. The principal advantage of a straightlined function over the curvelined one — according to J. Falewicz — lies in the possibility of making economic interpretations of the parameters of a straight line. In the traditional analysis of costs the fundamental research instruments are the individual costs and some other indices of exertion, as individual quantitative expenditures of productions goods, labour efficiency, labour absorbtion, the indice of rotation of turnover means a.s.o. The use of individual and other similar indices leads inevitably to fallacious plans and to misleading assessments about the enterprise's activities. It should be replaced by entirely free from any à priori assumptions. Such requirements are fulfilled by J. Falewicz's direct examination of interrelations between the global size of the variables of costs and production.